Expansion of the Adherence Club model for stable antiretroviral therapy patients in the Cape Metro, South Africa 2011–2015. Issue 6 (June 2016) - Wilkinson, Lynne; Harley, Beth; Sharp, Joseph; Solomon, Suhair; Jacobs, Shahieda; Cragg, Carol; Kriel, Ebrahim; Peton, Neshaan; Jennings, Karen; Grimsrud, Anna
Abstract: Objective: The ambitious '90‐90‐90' treatment targets require innovative models of care to support quality antiretroviral therapy (ART) delivery. While evidence for differentiated models of ART delivery is growing, there are few data on the feasibility of scale‐up. We describe the implementation of the Adherence Club (AC) model across the Cape Metro health district in Cape Town, South Africa, between January 2011 and March 2015. Methods: Using data from monthly aggregate AC monitoring reports and electronic monitoring systems for the district cohort, we report on the number of facilities offering ACs and the number of patients receiving ART care in the AC model. Results: Between January 2011 and March 2015, the AC programme expanded to reach 32 425 patients in 1308 ACs at 55 facilities. The proportion of the total ART cohort retained in an AC increased from 7.3% at the end of 2011 to 25.2% by March 2015. The number of facilities offering ACs also increased and by the end of the study period, 92.3% of patients were receiving ART at a facility that offered ACs. During this time, the overall ART cohort doubled from 66 616 to 128 697 patients. The implementation of the AC programme offset this increase by 51%. Conclusions: ACs now provide ART care to more than 30 000 patients. Further expansion of the model will require additional resources and support. More research is necessary to determine the outcomes and quality of care provided in ACs and other differentiated models of ART delivery, especially when implemented at scale.